Hippocampal theta in rats under urethane: generators and phase relations. - Green, K; Rawlins, J (1979)
Recordings were made from the directly visualized dorsal hippocampus of urethane-anesthetized rats with silver ball and tungsten microelectrodes. Theta of about 5 c/sec was elicited by reticular stimulation and was located in two broad strata in and subjacent to CA1. A superficial generator yielded 200-250 microV theta from the alveus, stratum oriens and stratum pyramidale; a null-theta and phase-reversal point was located in stratum radiatum; a deep generator yielded 300-500 microV theta in stratum lacunosum-moleculare of the hippocampus and distal stratum moleculare of the dentate gyrus, with maximum amplitude near the fissure. No theta was found in CA3. Cross-correlation analyses between generators yielded coefficients on the order of -0.80 while within a generator--especially the deep one--coefficients could reach +0.95. Phase analyses showed the two generators were about 180 degrees out of phase, with the deep generator leading. Septotemporal movement along the upper generator yielded no phase shifts; similar movement along the deep generator showed slight lead ing in septal portions. Subiculofimbrial movement in both generators showed a complex pattern of phase shifts: generally, subicular sites led fimbrial sites, but an inversion of 10 degrees-20 degrees occurred in the millimeter anterior to the center of the hippocampus. Anatomical, phase and other datal led to consideration of a possible retrohippocampal role in supplementing the well-known pacemaker in the medial septum.